(untitled) (Journal of EAHIL, 2017)
The EVLG (European Veterinary Libraries Group) had a very nice meeting outside the conference centre on the grass (and in the shade!). We elected some new board members and the board is now: Chair: Michael Eklund, Sweden Vicechair: Raisa Iivonen, Finland Secretary: Fiona Brown, Great Britain Webmanager: Eva Orban, Hungary Treasurer: Derek Halling, USA.